Measuring islanders' adaptive capacity towards the impact of climate change: a case of community in Langkawi Island - Hamdan, Mas Ernawati; Ahmad, Nobaya; Idris, Khairuddin; Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril (Human Resource Management Academic Research Society, 2018)
The progress of climate change is worsening and its formidable impacts would impinge the community’s socio-economic routines, especially those who rely heavily on nature stability. This study aims to measure Langkawi Island community’s adaptive capacity towards climate change impacts. This study is quantitative in nature whereby via a cluster random sampling, a total of 200 islanders was selected as respondents. The findings show Langkawi islanders had a moderate level of adaptive capacity in three aspects; cognitive, practices and structure. The study places a number of discussions and in anticipation, the findings and recommendations from this study can be referred to by any concerned parties when developing adaptation strategies for island communities.